Goal Directed Design Method on UI/UX Design Mobile-Based Application for Preventing Waste Dumping - Aliyah, Raden Ayu Alfirah; Indah, Dwi Rosa; Firdaus, Masagus Afriyan (ULTIMA InfoSys, 2024)
The issue of waste dumping persists a significant challenge in Indonesia, particularly in the context of South Sumatra Province. In 2022, the quantity of unmanaged waste in South Sumatra Province was documented at 521,075 tons per year. In the course of 2024, South Sumatra was subjected to a total of 58 floods. This illustrates that flooding remains a significant challenge that necessitates the development of innovative solutions, as it can impede the attainment of the Sustainable Development Goals (SDGs), particularly those pertaining to SDG 11, namely the maintenance of sustainable cities and communities. The act of discarding refuse into air ducts represents a significant contributing factor to the occurrence of flood disasters. Accordingly, this research was undertaken with the objective of designing an interface for the Jagoan Sungai application, which is intended to prevent waste dumping. The application was designed with the specific purpose of facilitating the reporting of instances of littering in river environments by individual communities. The application was designed using the Goal Directed Design method and subsequently evaluated using the User Experience Questionnaire (UEQ) method and the Think Aloud method. The UEQ test results indicate that the scores for the six scales exceed 0.8, indicating a high level of user satisfaction. The Think Aloud test results demonstrate that while no significant improvements are necessary, additional information should be incorporated into the application to enhance the user experience further.